Consequences of sex differences in Type I IFN responses for the regulation of antiviral immunity - Pujantell, Maria; Altfeld, Marcus (Frontiers in Immunology, 2022)
The immune system protects us from many pathogens, such as viruses. Antiviral immune mechanisms aim to limit viral replication, and must maintain immunological homeostasis to avoid excessive inflammation and damage to the host. Sex differences in the manifestation and progression of immune-mediated disease point to sex-specific factors modulating antiviral immunity. The exact mechanisms regulating these immunological differences between females and males are still insufficiently understood. Females are known to display stronger Type I IFN responses and are less susceptible to viral infections compared to males, indicating that Type I IFN responses might contribute to the sexual dimorphisms observed in antiviral responses. Here, we review the impact of sex hormones and X chromosome-encoded genes on differences in Type I IFN responses between females and males; and discuss the consequences of sex differences in Type I IFN responses for the regulation of antiviral immune responses.